Development of an accreditation model for health education and promotion programs in the Iranian primary healthcare system: a Delphi study - Farid Gharibi; Jafar Sadegh Tabrizi (Tabriz University of Medical Sciences, 2018)
Background: Considering the lack of accreditation models for health education and promotion(HEP) activities in the Iranian primary health care (PHC) system we conducted the present study to develop a national accreditation model for HEP actions in the Iranian PHC system.Methods: After a comprehensive review on the accreditation models in PHC field, especially those concentrated on the HEP programs, an initial HEP accreditation model was developed.Then, applying the Delphi technique, 18 experts in the Iranian PHC system with field experience in HEP programs were invited to assess the initial model. In the two-round Delphi study,aggregation was provided on the opinions and the standards and indicators were finalized.Conventional content analysis was applied to make sense of the data collected in the study.Results: The developed HEP accreditation model encompassed 62 indicators and five standards.The standards were as follow: "resources for HEP programs", "educational needs assessment of the target groups", "methods of providing a community with education", "management of health volunteers' actions" and "evaluation of HEP programs".Conclusion: The standards and indicators found in the present study may serve as an educational rationale for health educators while designing high-quality health education/promotion programs. This model may be helpful for health policy-makers and stakeholders while planning to assess the continuous quality improvement of HEP services delivered in the PHC systems.